Phytonutrients in Red Amaranth (Amaranthus cruentus, L.) and Feed Ratios Enhanced Rumen Fermentation Dynamics, Suppress Protozoal Population, and Methane Production - Ampapon, Thiwakorn; Viennasay, Bounnaxay; Matra, Maharach; Totakul, Pajaree; Wanapat, Metha (Frontiers in Animal Science, 2022)
The search for alternative modifiers of rumen fermentation to improve the production efficiency of livestock production is highly essential. This in vitro fermentation experiment was conducted using a factorial arrangement of two ratios of roughage to concentrate and seven levels of red amaranth (Amaranthus cruentus L.) leaf powder (RALP) as a percentage of total substrate in a completely randomized design (CRD). There were two factors: factor A was two ratios of roughage (R) to concentrate (C) at 60:40 and 40:60 and factor B was levels of RALP supplementation at 0, 2, 4, 6, 8, 10, and 12% dry matter (DM) of total dietary substrate. The results revealed that a R:C ratio at 40:60 increased rumen fermentation and reduced methane production (p < 0.05). The RALP incorporation as a feed additive was highly promising in enhancing propionate (C3) concentration, reducing acetate (C2) to (C3) ratio, and the protozoal population, while mitigating methane (CH4) production. Furthermore, DM degradation percentages were remarkably enhanced by increasing the RALP levels and R:C ratio at 40:60. In conclusion, plants rich in phytonutrients and minerals such as RALP and the lower R:C ratio showed a promising role in modulating rumen fermentation, mitigating methane production, as well as increasing substrate DM degradability.